Evaluating the effects of chloride on the performance of microbial fuel cells for wastewater treatment - Duyen T. M. To; Ngoc Pham; Hoa T. Pham (Vietnam Journal of Science, Technology and Engineering, 2022)
Water used in many industrial sectors such as processing and agriculture farming contain high salt concentrations. Without prior treatment, effluent discharge containing high salinity and high organic content can have dangerous effects on aquatic life, water portability, and agriculture. Up to 5% of wastewater generated worldwide is highly saline effluent. Microbial fuel cells (MFCs) have been considered as a promising saline wastewater treatment, which uses microorganisms to convert organic compounds into electrical energy. This study investigated lab-scale MFCs to evaluate the effect of chloride at different concentrations (0, 5, 10 and 20 g/l NaCl) on the performance of the MFC by examining its electrical generation and wastewater treatment efficiency. Increasing NaCl concentration led to a decrease in power generation with maximum power at 30, 18.7, 18.8, and 5.2 mW/m2 corresponding to 0, 5, 10, and 20 g/l of NaCl, respectively. The COD removal efficiency of the four treatments did not significantly vary (p>0.05) and reached 65.9% to 78.7%. Acidovorax spp. was isolated from the treatment without NaCl while Pseudomonas citronellolis was isolated from the treatments containing 10 and 20 g/l NaCl. Pseudomonas citronellolis can be used as a potential inoculum for MFCs treating highly saline wastewater based on its high electrical generation ability (606.8 mW/m2) based on inoculation of this pure strain into the mini MFC.